Les sources de la détérioration de la position relative des jeunes et des femmes sur le marché du travail au Québec - Guindon, Denis (L'Actualité économique, 1982)
AbstractThis study analyzes the causes of unemployment fluctuations in Quebec since 1962 according to age and sex. The author distinguishes between the cyclical and structural component of unemployment rates. Referring to the expansionary peak of 1966, he establishes that 50% of the rise in the female unemployment rate is of structural matter, whereas 80% of the rise in the youth unemployment rate comes from the demand deficiency.The structural factors appear in two groups of variables: the socio-demographic variables (the baby boom and the rise in the female participation rate) and the policy variables which include the generosity index of the unemployment insurance program, the relative minimum wage, and the relative earnings in the public and parapublic sector. This study shows that the policy factors have played a prominent part inside the structural component of unemployment rates during the 70's, especially for young men. Nearly 60% of the increase in the global structural unemployment rate since 1962 has been attributed to the government policies analyzed in this study, and nearly 30% has been issued solely from the government wage policy.For the author, the most important step to jump in order to improve the employment situation in Quebec remains the elimination of the three percentage points of purely cyclical unemployment that persisted in 1980 and 1981 (7 to 9 in 1982). The second one would be to bring back the average earnings in the public and parapublic sector closer to the average earnings in the private sector. The introduction of these policies coupled with the demographic forecast of StatisticsCanada would give a better employment surrounding for youth, but would only slow down the increase in the female unemployment rates.